Answer:
y = 1x/3 + 1/3
Step-by-step explanation:
First find the slope
m = (y_2 - y_1) / (x_2 - x_1)
We are given two points
( -4 , 1) ( 2 , 3)
x_1 = -4
y_1 = 1
x_2 = 2
y_2 = 3
Insert your values
m = (y_2 - y_1) / (x_2 - x_1)
m = ( 3 - 1) / ( 2 - (-4)
= 2/ 2 + 4
= 2 / 6
= 1/3
Step 2
y - y_1 = m(x - x_1)
y_1 = 1
x_1 = -4
m = 1/3
y - 1 = 1/3( x - (-4)
y - 1 = 1/3 (x + 4)( point slope form)
Open the bracket
y - 1 =( x + 4 )/ 3
y = (x + 4)/3 - 1
LCM = 3
y = (x + 4 - 3) / 3
y = (x + 1)/ 3
We can still separate
y = x/3 + 1/3
Following the equation of slope- intercept form
y = x/3 + 1/3(slope - intercept form)
y = 1x/3 + 1/3